Histological evidence for a supraspinous ligament in sauropod dinosaurs - Cerda, Ignacio Alejandro (2015)
Supraspinous ossified rods have been reported in the sacra of some derived sauropod dinosaurs. Although different hypotheses have been proposed to explain the origin ofthis structure, histological evidence has never been provided to support or reject any of them. In order to establish its origin, we analyse and characterize the microstructure of thesupraspinous rod of two sauropod dinosaurs from the Upper Cretaceous of Argentina. The supraspinous ossified rod is almost entirely formed by dense Haversian bone. Remains ofprimary bone consist entirely of an avascular tissue composed of two types of fibre-like structures, which are coarse and longitudinally (parallel to the main axis of the element) oriented. These structures are differentiated on the basis of their optical properties under polarized light. Very thin fibrous strands are also observed in some regions. These small fibres are all oriented parallel to one another but perpendicular to the element main axis. Histological features of the primary bone tissue indicate that the sacral supraspinous rod corresponds to an ossified supraspinous ligament. The formation of this structure appears to have been a non-pathological metaplastic ossification, possibly induced by the continuous tensile forces applied to the element.